Negative electrode material, preparation method thereof and lithium ion battery
By depositing silicon material in porous carbonaceous material to form a negative electrode material with a connecting pore network, the problem of uneven distribution of silicon and carbon in the existing silicon-carbon anode materials is solved, and the circulation performance and structural stability of the material are improved.
Patent Information
- Application Number
- CN202311228402.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
The dispersion uniformity of silicon and carbon in existing silicon-carbon anode materials is poor and the silicon particle size is too large, resulting in poor circulation performance and high expansion, which cannot meet the needs of high-energy-density lithium-ion batteries.
Porous carbonaceous material is used as the framework, and deposition is carried out in pores of different pore sizes through a silicon source to form a negative electrode material with a connecting pore network. The silicon material is distributed in different pores of the porous carbonaceous material to ensure that the pores are uniformly distributed and relatively dense.
The capacity performance, expansion performance, structural stability and circulation performance of the negative electrode material are improved, the risk of volume expansion and crushing is reduced, and the transmission efficiency of lithium ions is enhanced.
Smart Images

Figure CN119674051A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of negative electrode materials, and in particular relates to a negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Silicon-based negative electrode materials have the advantages of high specific capacity, low voltage platform, environmental friendliness and abundant resources. They are expected to replace graphite negative electrodes in the next generation of high specific energy lithium-ion batteries. However, silicon has poor conductivity and a huge volume effect during the charging and discharging process, which can easily lead to electrode polarization, material pulverization, SEI film reconstruction, low Coulomb efficiency and continuous capacity decay. In order to solve these problems, researchers have proposed a variety of solutions to combine metals, oxides, organic polymers, carbon and other materials with silicon to alleviate its volume changes and improve electrochemical stability. Among them, carbon materials have excellent conductivity and mechanical properties. Composites with silicon can not only effectively alleviate volume expansion, but also improve electrode conductivity and obtain stable SEI films. Silicon-carbon composite materials are the first silicon-based negative electrode materials to enter commercialization. However, the existing silicon-carbon negative electrode materials have poor uniformity in the dispersion of silicon and carbon, the particle size of silicon particles in the silicon-carbon negative electrode materials is too large, and the physical bonding between silicon and carbon in the silicon-carbon negative electrode materials deteriorates during the cycle, causing the separation of silicon and carbon and loss of electrical contact. These reasons lead to poor cycle performance and high expansion of the negative electrode materials, which cannot meet the needs of existing high-energy-density lithium-ion batteries.
[0003] Therefore, there is an urgent need for a silicon-carbon negative electrode material with low expansion, high capacity and excellent cycle performance. Summary of the invention
[0004] The purpose of the present application is to provide a negative electrode material and a preparation method thereof, and a lithium-ion battery, which can improve the capacity performance, expansion performance, structural stability and cycle performance of the negative electrode material.
[0005] In a first aspect, an embodiment of the present application provides a negative electrode material, which includes a porous carbonaceous material and a silicon material. The negative electrode material has a first region located in the central region inside the porous carbonaceous material, a second region distributed on the surface of the first region, and a third region distributed on the surface of the second region. The porous carbonaceous material located in the first region has first pores, the porous carbonaceous material located in the second region has second pores, and the porous carbonaceous material located in the third region has third pores. At least part of the first pores are connected to the second pores, at least part of the second pores are connected to the third pores, and at least part of the third pores are connected to the surface of the negative electrode material. The silicon material is distributed in at least one of the first pores, the second pores and the third pores. The pore diameter of the first pore is 0.1nm~2.2nm, the pore diameter of the second pore is 1.8nm~5nm, and the pore diameter of the third pore is 3nm~60nm. The probability entropy H of the pores in the porous carbonaceous material satisfies: 0.96>H>0.70.
[0006] In some embodiments, the negative electrode material includes at least one of the following features (1) to (14):
[0007] (1) the first pores include micropores, and the number of micropores in the first pores accounts for more than 60% based on the total number of pores in the first pores being 100%;
[0008] (2) the first pores include mesopores, and the number of mesopores in the first pores accounts for 5% to 40% based on the total number of pores in the first pores being 100%;
[0009] (3) the second pores include micropores, and the number of micropores in the second pores accounts for less than 70% based on the total number of pores in the second pores being 100%;
[0010] (4) the second pores include mesopores, and the number of mesopores in the second pores accounts for 30% to 90% based on the total number of pores in the second pores as 100%;
[0011] (5) the third pores include macropores, and the number of macropores in the third pores accounts for less than 20% based on the total number of pores in the third pores being 100%;
[0012] (6) The third pores include mesopores, and the number of mesopores in the third pores accounts for 80% to 95% based on the total number of pores in the third pores as 100%;
[0013] (7) The volume ratio of the first region, the second region and the third region is (0.6-0.8): (0.1-0.4):
[0014] (0 to 0.1) (excluding 0);
[0015] (8) The thickness H1 of the first region, the thickness H2 of the second region, and the thickness H3 of the third region satisfy: H1 > H2 > H3;
[0016] (9) The thickness H3 of the first region is 130 nm to 13000 nm;
[0017] (10) The thickness H2 of the second region is 50 nm to 2000 nm;
[0018] (11) The thickness H1 of the third region is 20 nm to 1000 nm;
[0019] (12) The pores in the porous carbonaceous material include open pores, and the proportion of the number of open pores in the total number of pores in the porous carbonaceous material is 82% to 99%;
[0020] (13) The pores in the porous carbonaceous material include open pores, and the volume proportion of open pores with a pore diameter of 0.2 nm to 10 nm in the total pores of the porous carbonaceous material is 50% to 80%;
[0021] (14) The pores in the negative electrode material include open pores, and the volume proportion of open pores with a pore diameter of 0.5 nm to 5 nm in the total pores of the negative electrode material is 55% to 75%.
[0022] In some embodiments, the negative electrode material includes at least one of the following features (1) to (23):
[0023] (1) The silicon material is also disposed on the surface of the porous carbonaceous material;
[0024] (2) The porous carbonaceous material includes at least one of petrochemical carbon, wood carbon, and polymer carbon;
[0025] (3) The silicon material includes at least one of silicon, SiO x (0 < x < 2), and silicon alloy;
[0026] (4) The particle size of the silicon material is 50% to 100% of the pore diameter of the porous carbonaceous material;
[0027] (5) The median particle size of the silicon material is 1 nm to 50 nm;
[0028] (6) The morphology of the porous carbonaceous material includes at least one of spherical and quasi-spherical;
[0029] (7) The median particle size of the porous carbonaceous material is 0.2 μm to 20 μm;
[0030] (8) The standard deviation of the directional distribution of pores in the porous carbonaceous material is 0.5% to 2.0%;
[0031] (9) The two-dimensional porosity of the porous carbonaceous material is 40% to 65%;
[0032] (10) The three-dimensional porosity of the porous carbonaceous material is 45% to 70%;
[0033] (11) The porous carbonaceous material accounts for 25% to 75% by mass of the negative electrode material;
[0034] (12) The mass proportion of the silicon material in the negative electrode material is 25% to 75%;
[0035] (13) The mass ratio of silicon element to carbon element in the negative electrode material is (0.8-1.5):1;
[0036] (14) The pore size of the porous carbonaceous material is 0.05 nm to 80 nm;
[0037] (15) The porous carbonaceous material is measured by X-ray diffraction, and the interlayer spacing of the (002) plane is 0.3 nm to 0.5 nm;
[0038] (16) The specific surface area of the porous carbonaceous material is 1000 m 2 / g~3000m 2 / g;
[0039] (17) The fixed carbon content of the porous carbonaceous material is greater than or equal to 99.5%;
[0040] (18) The pore volume of the porous carbonaceous material is greater than or equal to 0.6 cm 3 / g;
[0041] (19) In the porous carbonaceous material, sp 3 The content of hybrid carbon is 50% to 80%;
[0042] (20) The two-dimensional porosity of the negative electrode material is 1% to 30%;
[0043] (21) The three-dimensional porosity of the negative electrode material is 2% to 25%;
[0044] (22) The specific surface area of the negative electrode material is 1.5 m 2 / g~100m 2 / g;
[0045] (23) The median particle size of the silicon material is 1 nm to 50 nm.
[0046] In some embodiments, the negative electrode material further includes a carbon intermediate layer disposed between the silicon material and a pore wall of at least one of the first pore, the second pore, and the third pore;
[0047] The negative electrode material includes at least one of the following features (1) to (3):
[0048] (1) The material of the carbon intermediate layer includes at least one of carbon nanotubes, carbon fibers and graphene;
[0049] (2) The fixed carbon content of the carbon intermediate layer is greater than or equal to 99%;
[0050] (3) The thickness of the carbon intermediate layer is 0.1 nm to 5 nm.
[0051] In some embodiments, the negative electrode material further includes a coating layer disposed on the surface of the porous carbonaceous material, and the negative electrode material includes at least one of the following features (1) to (3):
[0052] (1) The material of the coating layer includes at least one of carbon black, graphite, carbon fiber, carbon nanotube and graphene;
[0053] (2) The coating layer has a thickness of 2 nm to 100 nm;
[0054] (3) The coating layer accounts for 1% to 10% by mass of the negative electrode material.
[0055] In a second aspect, an embodiment of the present application provides a method for preparing a negative electrode material, comprising the following steps:
[0056] A porous carbonaceous material is provided, wherein the porous carbonaceous material has a first region located in the central region inside the negative electrode material, a second region distributed on the surface of the first region, and a third region distributed on the surface of the second region, the porous carbonaceous material located in the first region has a first pore, the porous carbonaceous material located in the second region has a second pore, the porous carbonaceous material located in the third region has a third pore, at least part of the first pore is connected to the second pore, at least part of the second pore is connected to the third pore, at least part of the third pore is connected to the surface of the porous carbonaceous material, the pore size of the first pore is 0.1nm-2.2nm, the pore size of the second pore is 1.8nm-5nm, the pore size of the third pore is 3nm-60nm, and the probability entropy H of the pores in the porous carbonaceous material satisfies: 0.96>H>0.70;
[0057] A silicon source is used to perform a first deposition process in at least one of the first pores, the second pores and the third pores of the porous carbonaceous material to obtain a negative electrode material.
[0058] In some embodiments, the preparation method includes at least one of the following features (1) to (5):
[0059] (1) The first deposition process comprises chemical vapor deposition;
[0060] (2) The temperature of the first deposition treatment is 375° C. to 625° C.;
[0061] (3) The first deposition treatment time is 1 h to 20 h;
[0062] (4) The silicon source comprises at least one of monosilane and disilane;
[0063] (5) The inlet flow rate of the silicon source is 0.1 L / min to 10 L / min.
[0064] In some embodiments, before performing a first deposition process in at least one of the first pores, the second pores, and the third pores of the porous carbonaceous material using a silicon source, the method further includes: performing a second deposition process in at least one of the first pores, the second pores, and the third pores of the porous carbonaceous material using a first carbon source;
[0065] The preparation method comprises at least one of the following features (1) to (6):
[0066] (1) The first carbon source includes gaseous hydrocarbons;
[0067] (2) the first carbon source comprises gaseous hydrocarbons, wherein the gaseous hydrocarbons comprise at least one of methane, ethane, propane, ethylene, propylene, acetylene and propyne;
[0068] (3) The flow rate of the first carbon source is 0.1 L / min to 20 L / min;
[0069] (4) the second deposition process comprises at least one of a physical vapor deposition method and a chemical vapor deposition method;
[0070] (5) The temperature of the second deposition treatment is 600° C. to 1200° C.;
[0071] (6) The second deposition treatment time is 1 hour to 20 hours.
[0072] In some embodiments, after performing a first deposition process in at least one of the first pores, the second pores, and the third pores of the porous carbonaceous material using a silicon source, the method further includes: performing a third deposition process on the surface of the porous carbonaceous material using a second carbon source;
[0073] The preparation method comprises at least one of the following features (1) to (4):
[0074] (1) the second carbon source comprises at least one of pamine, resorcinol-formaldehyde resin, glucose, sucrose, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, asphalt, anthracene, aniline, methanol, ethanol, acetic acid, sodium acetate, methane, ethane, propane, ethylene, propylene, propyne or acetylene;
[0075] (2) the third deposition process comprises chemical vapor deposition;
[0076] (3) The temperature of the third deposition process is 600° C. to 1200° C.;
[0077] (4) The duration of the third deposition treatment is 0.5 h to 5 h.
[0078] In a third aspect, an embodiment of the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode material described in the first aspect or the negative electrode material prepared by the preparation method described in the second aspect.
[0079] Compared with the prior art, the present invention has the following beneficial effects:
[0080] In the negative electrode material of the present application, the first pores, the second pores and the third pores with different pore sizes are distributed in different areas of the porous carbonaceous material, and at least part of the first pores are connected to the second pores, at least part of the second pores are connected to the third pores, and at least part of the third pores are connected to the surface of the negative electrode material. The silicon material is distributed in at least one of the first pores, the second pores and the third pores. The probability entropy H of the pores in the porous carbonaceous material satisfies: 0.96>H>0.70, so that the porous carbonaceous material has a relatively uniform pore distribution and a relatively dense structure, and the porous carbonaceous material has a tendency of increasing pore size from the inside to the surface of the porous carbonaceous material, so that the first pores, the second pores and the third pores are connected to form a pore network, which can provide a continuous conductive channel. In addition, silicon particles are distributed in at least one of the first pores, the second pores and the third pores. The presence of the first pores, the second pores and the third pores can produce capillary action to absorb part of the electrolyte, increase the electrolyte retention capacity, and help to improve the cycle life of the negative electrode material. The negative electrode material of the present application is a negative electrode material with a relatively dense structure, which is conducive to controlling the transmission degree of lithium ions, ensuring the effectiveness of lithium ion embedding and extraction, and ensuring the low expansion and structural stability of the negative electrode material; the pore size distribution law of the first pore, the second pore and the third pore of the present application is not only conducive to the infiltration of silicon materials, but also can greatly buffer the volume expansion of silicon materials, reduce the volume expansion and even breakage of negative electrode materials, and at the same time make silicon and carbon evenly distributed, improve the cycle performance of negative electrode materials, and also make silicon materials better maintain volume during expansion, prevent the problem of material structure rupture or crushing caused by large volume changes of negative electrode materials, that is, the pore distribution of porous carbonaceous materials with different pore sizes can ensure the structural strength of porous carbonaceous materials, can reduce the possibility of structural collapse of negative electrode materials in the compaction process of preparing electrodes, and improve the structural stability of negative electrode materials. In summary, the negative electrode material of the present application has a high specific capacity, a low expansion rate, and excellent cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0082] Figure 1 This is a schematic diagram of the structure of the negative electrode material of this application;
[0083] Figure 2 This is a flow chart for preparing the negative electrode material of this application.
[0084] Figure 1 middle:
[0085] 1-porous carbonaceous materials;
[0086] 11- First area;
[0087] 12- first pore;
[0088] 13-Second area;
[0089] 14- second aperture;
[0090] 15- Third area;
[0091] 16-third pore;
[0092] 2-Silicon material. DETAILED DESCRIPTION
[0093] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0094] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0095] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0096] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0097] The present application embodiment provides a negative electrode material, such as Figure 1 As shown, the negative electrode material includes a porous carbonaceous material 1 and a silicon material 2. The negative electrode material has a first region 11 located in the central region of the porous carbonaceous material 1, a second region 13 distributed on the surface of the first region 11, and a third region 15 distributed on the surface of the second region 13. The porous carbonaceous material 1 located in the first region 11 has a first pore 12, the porous carbonaceous material 1 located in the second region 13 has a second pore 14, and the porous carbonaceous material 1 located in the third region 15 has a third pore 16. At least part of the first pore 1 2 is connected to the second pore 14, at least part of the second pore 14 is connected to the third pore 16, at least part of the third pore 16 is connected to the surface of the negative electrode material, the silicon material 2 is arranged in at least one of the first pore 12, the second pore 14 and the third pore 16, the pore diameter of the first pore 12 is 0.1nm~2.2nm, the pore diameter of the second pore 14 is 1.8nm~5nm, the pore diameter of the third pore 16 is 3nm~60nm, and the probability entropy H of the pores in the porous carbonaceous material 1 satisfies: 0.96>H>0.70.
[0098] In the above scheme, the negative electrode material of the present application, the first pores 12, the second pores 14 and the third pores 16 of different pore sizes are distributed in different areas of the porous carbonaceous material 1, and at least part of the first pores 12 are connected to the second pores 14, at least part of the second pores 14 are connected to the third pores 16, and at least part of the third pores 16 are connected to the surface of the negative electrode material, the silicon material 2 is distributed in the pore walls of at least one of the first pores 12, the second pores 14 and the third pores 16, and the probability entropy H of the pores in the porous carbonaceous material 1 satisfies: 0.96>H>0.70, so that the porous carbonaceous material 1 has a relatively uniform pore distribution and a relatively dense structure, and the porous carbonaceous material 1 has a tendency of increasing pore size from the inside to the surface of the porous carbonaceous material 1, so that the first pores 12, the second pores 14 and the third pores 16 are connected to form a pore network, which can provide a continuous conductive channel. Silicon particles are distributed in the first pore 12, the second pore 14 and the third pore 16. The presence of the first pore 12, the second pore 14 and the third pore 16 can produce capillary action to absorb part of the electrolyte, increase the electrolyte retention, and help control the degree of lithium ion transmission, ensure the effectiveness of lithium ion insertion and extraction, and ensure the low expansion and structural stability of the negative electrode material. The pore size distribution of the first pore 12, the second pore 14 and the third pore 16 of the present application is not only conducive to the infiltration of the silicon material 2, but also can greatly buffer the volume expansion of the silicon material 2, reduce the volume expansion and even crushing of the negative electrode material, and at the same time make silicon and carbon evenly distributed, improve the cycle performance of the negative electrode material, and also make the silicon material 2 better maintain its volume during the expansion process, and prevent the material structure from being broken or crushed due to the large volume change of the negative electrode material. That is, the pore distribution of the porous carbonaceous material 1 with different pore sizes can ensure the structural strength of the porous carbonaceous material 1, and can reduce the possibility of structural collapse of the negative electrode material during the compaction process of preparing the electrode, and improve the structural stability of the negative electrode material. In summary, the negative electrode material of the present application has a higher specific capacity, a lower expansion rate, and excellent cycle performance and rate performance.
[0099] It is understood that there may be no substantial interface between the first region 11, the second region 13 and the third region 15 in the porous carbonaceous material 1. In some embodiments, the porous carbonaceous material 1 may be automatically analyzed by software to artificially divide the three regions, such as Figure 1As shown, there are two dotted lines inside the porous carbonaceous material 1, and the porous carbonaceous material 1 is divided into three different areas by the two dotted lines. Statistical analysis is performed on the different areas, and quantitative results are output. Specifically, various images of porous carbonaceous materials 1 are input into the machine learning system by means of machine learning. On this basis, image recognition software is used to automatically identify particles and pores, and the geometric parameters of the pores are counted: the number of pores, area, length, width, orientation, shape coefficient, etc., and further statistics are obtained to obtain statistical parameters such as the content (porosity) of pores in the porous carbonaceous material 1, probability entropy, fractal dimension, and area probability distribution index, so as to obtain a distribution diagram of the pore size and shape coefficient. Through the probability distribution index and fractal dimension, those skilled in the art can clearly see how the size and shape of the pores change, thereby screening out the pores with a diameter from the center to the surface of the porous carbonaceous material 1. A porous carbonaceous material 1 with a trend of gradually increasing pore size is divided into a first region 11, a second region 13 and a third region 15 according to the pore size distribution specified in the present application. Usually, screening is performed from the geometric center of the porous carbonaceous material 1 to the surface. Starting from the geometric center of the porous carbonaceous material 1, the area satisfying the first pore 12 is screened and divided into the first region 11. Then, the screening is continued to be expanded from the edge of the first region 11 toward the surface of the porous carbonaceous material 1, and the area satisfying the second pore size is divided into the second region 13. Then, the screening is continued to be expanded from the edge of the second region 13 toward the surface of the porous carbonaceous material 1, and the area satisfying the third pore size is divided into the third region 15.
[0100] In the porous carbonaceous material 1, at least part of the first pore 12 is connected to the second pore 14, at least part of the second pore 14 is connected to the third pore 16, and at least part of the third pore 16 is connected to the surface of the negative electrode material, indicating that there are inevitably closed pores in the porous carbonaceous material 1 of the present application. The presence of closed pores cannot make the silicon material 2 fill, reducing the silicon loading of the material. At the same time, the presence of closed pores reduces the energy density and mechanical strength of the negative electrode material particles, so that the negative electrode material will cause the particles to be crushed during the rolling process of preparing the pole piece. Therefore, it is necessary to reduce the number of closed pores in the porous carbonaceous material 1 as much as possible. Preferably, the first pore 12, the second pore 14 and the third pore 16 are all open pores, and the pore size of the open pores in the porous carbonaceous material 1 is between 0.1nm and 60nm, and the open pores can be but are not limited to cross-linked holes, through holes and blind holes.
[0101] In the present application, the probability entropy H of the pores in the porous carbonaceous material 1 satisfies: 0.96>H>0.70, which can be specifically 0.75, 0.85, 0.9, 0.95 or 0.96, etc. Of course, it can also be other values within the above range. The present application is not limited here. Within the above-mentioned limited range, it shows that the pore direction of the pores in the porous carbonaceous material 1 of the present application is relatively random, the arrangement disorder of the pores in the porous carbonaceous material 1 is relatively high, the distance between each pore is relatively stable, the pore distribution is relatively uniform, and there is no obvious pore aggregation phenomenon. The silicon material 2 is distributed in the above-mentioned pores, which can make the silicon and carbon dispersed evenly and improve the cycle performance of the negative electrode material. If the probability entropy H of the pores in the porous carbonaceous material 1 is less than or equal to 0.7, the pores are prone to aggregation (several pores are connected, resulting in a pore size that is too large), causing the silicon material 2 to agglomerate in the pores and uneven stress distribution in all directions of the silicon material 2, which in turn causes uneven stress distribution inside the negative electrode material. Cracks are prone to occur in areas where more silicon material 2 is aggregated and in areas where the stress distribution of the silicon material 2 is uneven, causing the negative electrode material particles to be pulverized, the electrolyte to easily penetrate, resulting in an increase in the SEI film thickness, and poor electrochemical performance of the negative electrode material.
[0102] Probability entropy is used to describe the orientation of pores, represented by H. Orientation is opposite to randomness and is used to characterize the uniformity of pore distribution. It is defined as: Where n = 18, P i is the pore percentage in a specific direction interval, that is, P i is the ratio of the area of pores in a specific direction interval to the total area of pores in the porous carbonaceous material 1, i represents a specific direction interval, i = 0° ~ 180°, which means: for any two-dimensional cross-section material, its geometric center is taken as the center of the circle, and any radial direction is defined as 0°, and then rotated with the center of the circle as the center, and a region is divided every 10°, and a total of 18 regions are divided. The specific direction interval is any one of the above 18 regions. For example, taking the specific direction interval within the range of 0° ~ 10° as an example, that is, i = 10°, the pore percentage P in the specific direction interval of 0° ~ 10° is calculated. 10° , the porosity was measured by ImageJ image processing software: the two-dimensional cross-sectional particle image of the porous carbonaceous material 1 was first converted into a grayscale image to improve the accuracy of image measurement, and the ratio of the grayscale area of a specific grayscale region (0° to 10°) to the total grayscale area of the two-dimensional cross-sectional particle image was measured by the “Grayscale Ratio” option in the “Measurement” toolbar of the ImageJ image processing software, i.e., P 10°In the present application, when H=0, the pore orientation of the material is the strongest, all pores in the material have the same arrangement direction, and they tend to gather in a certain direction in the material; when H=1, the pore orientation of the material is the weakest, all pore directions in the material tend to be random, and the pore distribution is uniform. The smaller H is, the more obvious the pore orientation is, and the easier it is for the pores in the material particles to gather in a certain direction, forming a segregation phenomenon.
[0103] In some embodiments, the first pore 12 includes mesopores and / or micropores, and the total number of pores in the first pore 12 is 100%, and the number of micropores in the first pore 12 accounts for more than 60%, and can be 65%, 70%, 73%, 78%, 85%, 90% or 95%, etc., and can be other values within the above range, which is not limited in this application. Taking the total number of pores in the first pore 12 as 100%, the number of mesopores in the first pore 12 accounts for 5% to 40%, and can be 5%, 10%, 20%, 30% or 40%, etc., and can be other values within the above range, which is not limited in this application. Within the above-mentioned limit range, it indicates that the first pores 12 with a micropore diameter account for a larger proportion, that is, the pore diameter of the first pores 12 is smaller, and the first pores 12 are closer to the center of the porous carbonaceous material 1 than the second pores 14 and the third pores 16, so that the pore diameter of the pores in the central area of the porous carbonaceous material 1 is smaller, which can ensure the mechanical strength of the porous carbonaceous material 1.
[0104] In some embodiments, the second pores 14 include mesopores and / or micropores, and the total number of pores in the second pores 14 is 100%, and the number of micropores in the second pores 14 accounts for less than 70%, and can be 30%, 40%, 50%, 60% or 68%, etc., and can be other values within the above range, which is not limited in this application. Taking the total number of pores in the second pores 14 as 100%, the number of mesopores in the second pores 14 accounts for 30% to 90%, and can be 30%, 40%, 50%, 60%, 70%, 80% or 90%, etc., and can be other values within the above range, which is not limited in this application.
[0105] In some embodiments, the third pore 16 includes mesopores and / or macropores. Taking the total number of pores in the third pore 16 as 100%, the number of macropores in the third pore 16 accounts for less than 20%, which can be 3%, 5%, 10%, 15% or 18%, etc., and can be other values within the above range, which is not limited in this application. Taking the total number of pores in the third pore 16 as 100%, the number of mesopores in the third pore 16 accounts for 80% to 95%, which can be 80%, 83%, 85%, 90%, 92%, 84% or 95%, etc., and can be other values within the above range, which is not limited in this application. Within the above-mentioned limited range, it shows that the third pore 16 is mainly mesopores, which can provide space for silicon expansion and form lithium insertion channels, while ensuring the structural strength of the porous carbonaceous material 1.
[0106] The number ratio of the above-mentioned pores is detected and calculated by the following method: on the basis of the divided first area 11, the second area 13 and the third area 15, the pores in each first area 11, the second area 13 and the third area 15 are calculated respectively by Thermo Scientific Avizo software, PCAS software and Avizo software, and then the number of micropores and mesopores in the first area 11, the number of micropores and mesopores in the second area 13 and the number of macropores and mesopores in the third area 15 are identified by setting the pore size threshold, wherein the pore size threshold of the micropores is set to a pore size less than 2 nm, the pore size threshold of the mesopores is set to a pore size of 2 nm to 50 nm, and the pore size threshold of the macropores is set to a pore size greater than 50 nm. Finally, the ratio of the number of pores (micropores, mesopores or macropores) to be calculated in each area to the total number of pores in the corresponding area is calculated. It can be understood that the pores of the porous carbonaceous material 1 of the present application include micropores, mesopores and macropores. Micropores refer to pores with a pore size less than 2nm, mesopores refer to pores with a pore size between 2nm and 50nm, and macropores refer to pores with a pore size greater than 50nm. Mesopores and macropores can provide more space for the expansion of silicon material 2. Macropores, mesopores and silicon material 2 in the pores can provide a certain space for the expansion of the material during the charging and discharging process, thereby alleviating the volume expansion of the material during the charging and discharging process. In addition, the presence of macropores and mesopores is beneficial to the continuous infiltration of gaseous silicon sources in the negative electrode material during the preparation process, thereby increasing the silicon loading capacity. The micropores and the silicon material 2 filled in the micropores can ensure the structural density of the porous carbonaceous material 1, so that the negative electrode material will not collapse during the compaction process of preparing the electrode.
[0107] In some embodiments, the average pore size of the first pores 12 is 0.1 nm to 2.2 nm, and may be 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm or 2.2 nm, etc. Of course, it may also be other values within the above range, which is not limited here.
[0108] In some embodiments, the average pore size of the second pores 14 is 1.8 nm to 5 nm, and can be specifically 1.8 nm, 2.3 nm, 2.5 nm, 3 nm, 3.5 nm, 3.8 nm, 4.2 nm, 4.7 nm or 5 nm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0109] In some embodiments, the average pore size of the third pore 16 is 3 nm to 60 nm, and can be 3 nm, 8 nm, 15 nm, 20 nm, 30 nm, 40 nm, 50 nm or 60 nm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0110] In some embodiments, the volume ratio of the first region 11, the second region 13 and the third region 15 is (0.6-0.8): (0.1-0.4): (0-0.1) (excluding 0), and the volume ratio of the first region 11, the second region 13 and the third region 15 can be specifically 0.7: 0.3: 0.1, 0.8: 0.1: 0.1 or 0.6: 0.35: 0.5, etc., and of course it can also be other values within the above range, which are not limited here. Within the above-mentioned limited range, it shows that the volume of the first region 11> the volume of the second region 13> the volume of the third region 15, indicating that the pores in the porous carbonaceous material 1 of the present application are mainly micropores, and the proportion of mesopores and macropores decreases successively, which can ensure the smooth infiltration of gas into the negative electrode material during use, and the pores inside the particles will not be too large or too many.
[0111] The volumes of the first region 11, the second region 13 and the third region 15 of the present application are calculated with the assistance of ImageJ software. The areas of the first region 11, the second region 13 and the third region 15 are calculated respectively after sectioning the porous carbonaceous material 1, and then the areas are multiplied by the thickness of each region to obtain the volumes of the first region 11, the second region 13 and the third region 15, and then the volume ratio of the first region 11, the second region 13 and the third region 15 is calculated.
[0112] In some embodiments, the thickness H1 of the first region 11, the thickness H2 of the second region 13, and the thickness H3 of the third region 15 satisfy: H1>H2>H3. The thickness of the first region 11 is the largest, the second region 13 is the second, and the thickness of the third region 15 is the smallest, which can ensure the gradient deposition of silicon particles in the porous carbonaceous particles, which is beneficial to improving the specific capacity of the negative electrode material and the overall performance of the battery.
[0113] In some embodiments, the thickness H1 of the first region 11 is 130nm to 13000nm, and may be 50nm, 100nm, 300nm, 500nm, 8000nm, 1000nm, 3000nm, 5000nm, 10000nm or 13000nm, etc. Of course, it may also be other values within the above range, which is not limited here.
[0114] In some embodiments, the thickness H2 of the second region 13 is 50nm to 2000nm, and can be specifically 50nm, 100nm, 300nm, 500nm, 8000nm, 1000nm, 1200nm, 1500nm, 1800nm or 2000nm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0115] In some embodiments, the thickness H3 of the third region 15 is 20nm to 1000nm, and can be specifically 20nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm or 1000nm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0116] In some embodiments, the pores in the negative electrode material include open pores, and the number of open pores accounts for 82% to 99% of the total number of pores in the porous carbonaceous material 1, which can be 82%, 85%, 88%, 90%, 93%, 96% or 99%, etc., and of course, it can also be other values within the above range, which are not limited here. It can be understood that the pores in the negative electrode material include open pores and irreducible closed pores. Both open pores and closed pores can be used to alleviate volume expansion. In order to increase the load of the porous carbonaceous material 1 corresponding to the silicon material 2, the number of open pores in this application is much larger than the number of closed pores. If the number of open pores accounts for less than 82% of the total number of pores in the porous carbonaceous material 1, the silicon material 2 that can be accommodated is too small, which will affect the capacity density of the material. Preferably, the number of open pores accounts for 86% to 96% of the total number of pores in the porous carbonaceous material 1.
[0117] In some embodiments, the pore size of the opening is 0.1nm to 50nm, specifically 0.1nm, 0.5nm, 1nm, 5nm, 10nm, 20nm, 30nm, 40nm or 50nm, etc., and of course other values within the above range, which are not limited here. Within the above-defined range, it is conducive to the embedding of silicon particles, and a certain space can be reserved for buffering the volume expansion of the silicon material 2. If the pore size of the opening is greater than 50nm, the structure of the porous carbonaceous material 1 will be unstable and easy to collapse, and the silicon material 2 deposited in the hole will easily be segregated, resulting in uneven material expansion stress.
[0118] In some embodiments, the volume proportion of pores with a pore size of 0.2 nm to 10 nm in the total pores in the porous carbonaceous material 1 is 50% to 80%, specifically 50%, 55%, 60%, 70%, 75% or 80%, etc., and of course it can also be other values within the above range, which are not limited here. If the volume proportion of the openings with a pore size of 0.2nm to 10nm in the total pores of the porous carbonaceous material 1 is less than 50%, the pore size of the porous carbonaceous material 1 is concentrated in a smaller (0.1nm to 0.2nm) or larger (10nm to 50nm) range, resulting in uneven distribution of the pore size of the porous carbonaceous material 1, which in turn leads to different silicon loadings in different regions inside the porous carbonaceous material 1, resulting in poor diffusion distribution of silicon, resulting in deterioration of the electrochemical performance of the material; if the volume proportion of the openings with a pore size of 0.2nm to 10nm in the total pores of the porous carbonaceous material 1 is greater than 80%, the pore size distribution in the porous carbonaceous material 1 is too concentrated, and the gradient distribution of the pores cannot be achieved, resulting in deterioration of the electrochemical performance of the material. Preferably, the volume proportion of the openings with a pore size of 0.5nm to 5nm in the total pores of the porous carbonaceous material 1 is 55% to 75%.
[0119] In some embodiments, the porous carbonaceous material 1 includes at least one of petrochemical carbon, wood carbon and high molecular polymer carbon. For example, the petrochemical carbon is derived from cracking products such as coal, petroleum products and high molecular organic matter, the wood carbon is derived from coconut shells, peanut shells, plants and wood, and the high molecular polymer carbon is derived from phenolic resins, rubber and plastics.
[0120] In some embodiments, the silicon material 2 includes at least one of silicon, silicon oxide, and silicon alloy. Silicon oxide is a silicon-oxygen composite containing oxygen atoms and silicon atoms, and the molar ratio of oxygen atoms to silicon atoms is 0.5 to 2. It is usually expressed by the general formula SiOx (0.5≤x≤2), which can be a material formed by silicon particles dispersed in SiO2, or a material having a tetrahedral structural unit, in which the silicon atom is located at the center of the tetrahedral structural unit, and the silicon atom and the oxygen atom are located at the four vertices of the tetrahedral structural unit.
[0121] In some embodiments, the particle size of the silicon material 2 is 50% to 100% of the pore size of the porous carbonaceous material 1. The particle size of the silicon material 2 can be 50%, 60%, 70%, 80%, 90% or 100% of the pore size of the porous carbonaceous material 1, and of course it can also be other values within the above range, which are not limited here. Within the above-mentioned limited range, if the particle size of the silicon material 2 is smaller than the pore size of the porous carbonaceous material 1, the silicon material 2 is prone to capillary condensation in the pores of the porous carbonaceous material 1, which is conducive to increasing the deposition amount of the silicon material 2. If the particle size of the silicon material 2 is equivalent to the pores of the porous carbonaceous material 1, the pores have a very strong deposition ability for the silicon material 2, which is suitable for deposition at extremely low concentrations. If the particle size of silicon material 2 is less than 50% of the pore size of porous carbon material 1, that is, the particle size of silicon material 2 is much smaller than the pore size of porous carbon material 1, silicon material 2 is prone to desorption, resulting in a decrease in the deposition amount of silicon material 2. At the same time, the porous carbon material 1 reserves too much buffer space for the expansion of silicon material 2, resulting in a decrease in the volume energy density and structural stability of the material; if the particle size of silicon material 2 is larger than the pores of porous carbon material 1, silicon material 2 cannot be filled in the porous carbon material 1, resulting in too little silicon loading in the negative electrode material and too many pores in the porous carbon material 1, resulting in a decrease in the capacity performance and structural stability of the material.
[0122] In some embodiments, the median particle size of the silicon material 2 is 1nm to 50nm, specifically 1nm, 5nm, 10nm, 20nm, 30nm, 40nm or 50nm, etc., and of course other values within the above range, which are not limited here. If the median particle size of the silicon material 2 is less than 1nm, it will cause the segregation of nano-silicon inside the pores or the gap between the nano-silicon and the pore wall to be large, resulting in too little silicon loading, which will not only reduce the overall structural strength of the negative electrode material, but also reduce the specific capacity of the material; if the median particle size of the silicon material 2 is greater than 50nm, it will not be easy for the silicon material 2 to be embedded in the pores of the porous carbonaceous material 1, reducing the electrochemical performance of the negative electrode material.
[0123] In some embodiments, the present application does not limit the morphology of the porous carbonaceous material 1, including but not limited to at least one of a spherical shape and a spherical-like shape.
[0124] In some embodiments, the median particle size of the porous carbonaceous material 1 is 0.2 μm to 20 μm, specifically 0.2 μm, 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm or 20 μm, etc. Of course, it can also be other values within the above range, which are not limited here. If the median particle size of the porous carbonaceous material 1 is less than 0.2 μm, the particle size of the porous carbonaceous material 1 is too small, which increases the side reaction, resulting in the continuous thickening of the SEI film initially generated in the negative electrode material, and the continuously thickened SEI film causes the material to expand too much during the cycle; if the median particle size of the porous carbonaceous material 1 is greater than 20 μm, the particle size of the porous carbonaceous material 1 is too large, resulting in Li + The transmission distance in the negative electrode material is too long, which leads to poor kinetic performance and large polarization of the material.
[0125] In some embodiments, the standard deviation of the directional distribution of the pores in the porous carbonaceous material 1 is 0.5% to 2.0%, specifically 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8% or 2.0%, etc., and of course other values within the above range, which are not limited here. Within the above-defined range, it is shown that the distribution direction of the pores in the porous carbonaceous material 1 of the present application tends to be uniform overall, and there is almost no pore segregation phenomenon.
[0126] The size of the standard deviation of the oriented distribution can also reflect the strength of the pore orientation in the porous carbonaceous material 1. The oriented distribution standard deviation has the opposite meaning to the probability entropy. The larger the standard deviation of the oriented distribution of the pores in the porous carbonaceous material 1, the smaller the probability entropy, the stronger the orientation, the weaker the randomness of the pore distribution, the pores are prone to be concentrated in a certain direction, and the more uneven the pore distribution; the smaller the standard deviation of the oriented distribution of the pores in the porous carbonaceous material 1, the larger the probability entropy, the weaker the orientation, the stronger the randomness of the pore distribution, and the better the uniformity of the pore distribution. The calculation method of the standard deviation of the directional distribution is as follows: the orientation of the pores can be determined by counting the number of pores within a certain pore angle of the porous carbonaceous material 1. The pore angle is the angle between the major axis of the equivalent ellipse of the porous carbonaceous material 1 and the vertical line. In the present invention, the pore angle range is 0° to 180°, and every 10° is a calculation area. The percentage of the number of pores in each interval is counted, and the standard deviation of the number of pores in all intervals in each group is further calculated to obtain the standard deviation of the directional distribution of the pores in the porous carbonaceous material 1.
[0127] In some embodiments, the two-dimensional porosity of the porous carbonaceous material 1 is 40% to 65%, specifically 40%, 45%, 50%, 55%, 60% or 65%, etc., and of course, other values within the above range are also possible, which are not limited here. The two-dimensional porosity is the porosity obtained by cutting the porous carbonaceous material 1 and combining it with ImageJ image processing software.
[0128] In some embodiments, the three-dimensional porosity of the porous carbonaceous material 1 is 45% to 70%, specifically 45%, 50%, 55%, 60%, 65% or 70%, etc., and of course, it can also be other values within the above range, which are not limited here. The three-dimensional porosity refers to the real porosity of the porous carbonaceous material 1, which is obtained by micropore pore size distribution test (nitrogen adsorption and desorption curve).
[0129] In some embodiments, the two-dimensional porosity of the negative electrode material is 1% to 30%, specifically 1%, 5%, 10%, 15%, 20% or 30%, etc., and of course, it can also be other values within the above range, which is not limited here.
[0130] In some embodiments, the three-dimensional porosity of the negative electrode material is 2% to 25%, specifically 2%, 5%, 10%, 15%, 20% or 25%, etc., and of course other values within the above range are also possible, which are not limited here.
[0131] The porosity of the porous carbonaceous material 1 and the negative electrode material of the present application is appropriate, which does not affect the embedding of the silicon material 2 and can ensure the structural strength of the porous carbonaceous material 1.
[0132] In some embodiments, the mass proportion of the porous carbonaceous material 1 in the negative electrode material is 25% to 75%, specifically 25%, 35%, 45%, 50%, 65% or 75%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0133] In some embodiments, the mass proportion of silicon material 2 in the negative electrode material is 25% to 75%, specifically 25%, 35%, 45%, 50%, 65% or 75%, etc., and of course other values within the above range are also possible, which are not limited here.
[0134] In some embodiments, the mass ratio of silicon to carbon in the negative electrode material is (0.8-1.5):1, specifically 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc. Of course, it can also be other values within the above range, which is not limited here.
[0135] In some embodiments, the pore size of the porous carbonaceous material 1 is 0.05nm to 80nm, specifically 0.05nm, 0.1nm, 0.5nm, 1nm, 5nm, 10nm, 30nm, 50nm, 70nm or 80nm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0136] In some embodiments, the porous carbonaceous material 1 is measured by X-ray diffraction, and the interlayer spacing of the (002) plane is 0.3nm to 0.5nm, which can be 0.3nm, 0.33nm, 0.35nm, 0.40nm, 0.45nm, 0.48nm or 0.5nm, etc. Of course, it can also be other values within the above range, which are not limited here. Within the above-mentioned limited range, it is shown that the porous carbonaceous material 1 of the present application has a high degree of graphitization. In some embodiments, the specific surface area of the porous carbonaceous material 1 is 1000m 2 / g~3000m 2 / g, specifically 1000m 2 / g、1500m 2 / g, 2000m 2 / g, 2500m 2 / g or 3000m 2 / g, etc., and can certainly be other values within the above range, which are not limited here.
[0137] In some embodiments, the fixed carbon content of the porous carbonaceous material 1 is greater than or equal to 99.5%, specifically 99.5%, 99.6%, 99.7%, 99.8% or 99.9%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0138] In some embodiments, the pore volume of the porous carbonaceous material 1 is greater than or equal to 0.6 cm 3 / g, specifically 0.6cm 3 / g, 0.8cm 3 / g, 1cm 3 / g, 1.2cm 3 / g or 1.5cm 3 / g, etc., and can certainly be other values within the above range, which are not limited here.
[0139] In some embodiments, in the porous carbonaceous material 1, sp 3 The content of hybrid carbon is 50% to 80%, specifically 50%, 55%, 65%, 70%, 75% or 80%, etc. Of course, it can also be other values within the above range, which is not limited here.
[0140] In some embodiments, the specific surface area of the negative electrode material is 1.5 m 2 / g~100m 2 / g, specifically 1.5m 2 / g, 5m 2 / g, 10m 2 / g, 30m 2 / g, 50m 2 / g, 80m2 / g or 100m 2 / g, etc., and can certainly be other values within the above range, which are not limited here.
[0141] In some embodiments, the negative electrode material further includes a carbon intermediate layer disposed between the silicon material 2 and the pore wall of at least one of the first pore 12, the second pore 14, and the third pore 16. The presence of the carbon intermediate layer, on the one hand, can serve as a binder between the porous carbonaceous material 1 and the silicon material 2, can improve the interface state between the silicon material 2 and the porous carbonaceous material 1, enhance the affinity between the silicon material 2 and the porous carbonaceous material 1, make the silicon and carbon tightly connected, and facilitate the deposition of the silicon material 2 inside the pores of the porous carbonaceous material 1 to enhance the bonding strength between the silicon material 2 and the porous carbonaceous material 1, so that the silicon material 2 is not easy to fall off during the charge and discharge process of the negative electrode material. On the other hand, the carbon intermediate layer can form a conductive carbon network structure together with the porous carbonaceous material 1, improve the interface performance between the silicon material 2 and the electrolyte, and enhance the conductivity of the negative electrode material.
[0142] In some embodiments, the material of the carbon intermediate layer includes at least one of carbon nanotubes, carbon fibers and graphene.
[0143] In some embodiments, the fixed carbon content of the carbon interlayer is greater than or equal to 99%.
[0144] In some embodiments, the thickness of the carbon intermediate layer is 0.1nm to 5nm, specifically 0.1nm, 0.5nm, 1nm, 2nm, 3nm, 4nm or 5nm, etc., and of course other values within the above range can also be used, which are not limited here. The thickness of the carbon intermediate layer of the present application is relatively thin, which can meet the requirements of improving the interface state between the silicon material 2 and the porous carbonaceous material 1, while not allowing the silicon material 2 and the carbon intermediate layer to completely fill the pores of the porous carbonaceous material 1. On the one hand, it is convenient for the filling of the silicon material 2, and on the other hand, it reserves space for the expansion of the silicon material 2, which will not significantly affect the relative mass ratio between the silicon material 2 and the porous carbonaceous material 1, thereby ensuring that the specific surface area and pore size distribution of the negative electrode material are within a suitable range.
[0145] In some embodiments, the negative electrode material also includes a coating layer arranged on the surface of the porous carbonaceous material 1. On the one hand, the presence of the coating layer can improve the electronic conductivity of the negative electrode material. On the other hand, the coating layer can prevent the electrolyte from directly contacting the active material inside the coating layer, thereby reducing excessive contact between the electrolyte and the silicon material 2, and reducing the side reaction between the electrolyte and the silicon material 2 to produce a solid electrolyte interphase (SEI) film that consumes the electrolyte, which helps to extend the cycle life of the battery and improve the electrochemical properties of the material.
[0146] In some embodiments, the material of the coating layer includes at least one of hard carbon, soft carbon, carbon black, graphite, carbon fiber, carbon nanotube and graphene.
[0147] In some embodiments, the thickness of the coating layer is 2nm to 100nm, specifically 2nm, 10nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm, etc. Of course, it can also be other values within the above range, which is not limited here.
[0148] In some embodiments, the mass percentage of the coating layer in the negative electrode material is 1% to 10%, specifically 1%, 3%, 5%, 7% or 10%, etc., and of course other values within the above range are also possible, which are not limited here.
[0149] The present application also provides a method for preparing a negative electrode material. Figure 1 As shown, the following steps are included:
[0150] S100, providing a porous carbonaceous material 1, the porous carbonaceous material 1 comprising a first region 11 located in the central region of the porous carbonaceous material 1, a second region 13 covered on the surface of the first region 11, and a third region 15 covered on the surface of the second region 13, the porous carbonaceous material 1 located in the first region 11 has a first pore 12, the porous carbonaceous material 1 located in the second region 13 has a second pore 14, the porous carbonaceous material 1 located in the third region 15 has a third pore 16, the first pore 12 is connected to the second pore 14, the second pore 14 is connected to the third pore 16, the third pore 16 is connected to the surface of the negative electrode material, the pore diameter of the first pore 12 is 0.1nm-2.2nm, the pore diameter of the second pore 14 is 1.8nm-5nm, the pore diameter of the third pore 16 is 3nm-60nm, and the probability entropy H of the pores in the porous carbonaceous material 1 satisfies: 0.96>H>0.70;
[0151] S200 , using a silicon source to perform a first deposition process in at least one of the first pores 12 , the second pores 14 , and the third pores 16 of the porous carbonaceous material 1 , to obtain a negative electrode material.
[0152] In the above technical scheme, the present application selects a porous carbon material 1 with a specific distribution of pores of different pore sizes, and uses the above porous carbon material 1 as a skeleton to deposit silicon material 2 on the pore walls of the porous carbon material 1. First, the first pore 12, the second pore 14 and the third pore 16 are connected to form a pore network, which can provide a continuous conductive channel. Second, the pore size distribution of the first pore 12, the second pore 14 and the third pore 16 is conducive to the infiltration of the silicon material 2, which can greatly buffer the volume expansion of the silicon material 2 and reduce the problem of volume expansion or even breakage of the negative electrode material. Third, the pore distribution of the porous carbon material 1 with different pore sizes allows the silicon material 2 to better maintain its volume during the expansion process, preventing the problem of material structure rupture or crushing caused by the large volume change of the negative electrode material, that is, the pore distribution of the porous carbon material 1 with different pore sizes can ensure the structural strength of the porous carbon material 1, can reduce the possibility of structural collapse of the negative electrode material during the compaction process of preparing the electrode, and improve the structural stability of the negative electrode material. The preparation method of the present application has a simple process and can effectively solve the problem of poor cycle performance caused by uneven distribution of silicon and carbon in the silicon-carbon negative electrode material.
[0153] The preparation method of the present application is described in detail below with reference to the examples. Figure 2 As shown, the method for preparing the negative electrode material of the present application comprises the following steps:
[0154] S100. Provide a porous carbonaceous material 1, wherein the porous carbonaceous material 1 includes a first region 11 located in the central region inside the porous carbonaceous material 1, a second region 13 covered on the surface of the first region 11, and a third region 15 covered on the surface of the second region 13. The porous carbonaceous material 1 located in the first region 11 has a first pore 12, the porous carbonaceous material 1 located in the second region 13 has a second pore 14, and the porous carbonaceous material 1 located in the third region 15 has a third pore 16. The first pore 12 is connected to the second pore 14, the second pore 14 is connected to the third pore 16, and the third pore 16 is connected to the surface of the negative electrode material. The pore diameter of the first pore 12 is 0.1nm~2.2nm, the pore diameter of the second pore 14 is 1.8nm~5nm, and the pore diameter of the third pore 16 is 3nm~60nm. The probability entropy H of the pores in the porous carbonaceous material 1 satisfies: 0.96>H>0.70.
[0155] In this step, the porous carbonaceous material 1 can be obtained by screening or designed by additive manufacturing. The porous carbonaceous material 1 is produced by pyrolysis of an organic precursor at 500°C to 1500°C. The pore size of the porous carbonaceous material 1 is affected by the selection of raw materials and preparation parameters. Preferably, the organic precursor is an organic polymer material, and the organic polymer carbon is prepared by catalytic polymerization of organic small molecule monomers. Therefore, it has the advantages of being able to obtain carbon materials with regular morphology and a simple synthesis process, and is therefore an excellent precursor for preparing porous carbon materials. For example, it can be polyvinyl chloride, polypropylene, furan resin, phenolic resin, urea-formaldehyde resin, polycarbonate, polytetrafluoroethylene, etc. The present application can also be achieved by pre-designing a digital model of a porous carbonaceous material 1 that meets the requirements, then printing the finished product using a carbon material 3D printing device, and finally carbonizing it. For example, the carbon material can be ABS resin (acrylonitrile-butadiene-styrene copolymer). The present application selects and designs the pore size and distribution of the porous carbonaceous material 1 from a microscopic perspective, so that the pores and probability entropy of the porous carbonaceous material 1 can be flexibly adjusted to meet the needs.
[0156] It can be understood that there is no substantial interface between the first region 11, the second region 13 and the third region 15 in the porous carbonaceous material 1, and only artificial division is performed. The porous carbonaceous material 1 can be automatically analyzed by software, and the quantitative results can be output. Specifically, in the identification of particles and pores, various particles and pore images can be imported, and the particles and pores can be automatically removed by binarization, and the particles and pores can be automatically segmented and identified. The various geometric parameters of all particles and pores are displayed in the data table, including the number of particles and pores, area, length, width, orientation, shape coefficient, etc., and the statistical parameters such as particle and pore content (porosity), orientation probability entropy, fractal dimension and area probability distribution index are obtained, so that the distribution diagram of pore size and shape coefficient can be obtained. Through the probability distribution index and fractal dimension, those skilled in the art can clearly see how the size and shape of the pores change, so that the first region 11, the second region 13 and the third region 15 can be divided.
[0157] In some embodiments, before performing S200, the method further includes: performing a second deposition process using a first carbon source in at least one of the first pores 12, the second pores 14 and the third pores 16 of the porous carbonaceous material 1 to obtain a carbon intermediate layer.
[0158] In some embodiments, the first carbon source comprises a gaseous hydrocarbon comprising at least one of methane, ethane, propane, ethylene, propylene, acetylene, and propyne.
[0159] In some embodiments, the inlet flow rate of the first carbon source is 0.1 L / min to 20 L / min, specifically 0.0.1 L / min, 1 L / min, 3 L / min, 5 L / min, 8 L / min, 10 L / min, 13 L / min, 15 L / min, 18 L / min or 20 L / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0160] In some embodiments, the second deposition treatment includes at least one of physical vapor deposition and chemical vapor deposition. Exemplarily, the physical vapor deposition method includes vacuum evaporation, arc ion plating, magnetron sputtering, molecular beam epitaxy and pulsed laser deposition, etc.; the chemical vapor deposition method includes atmospheric pressure chemical vapor deposition, low pressure chemical vapor deposition, plasma chemical vapor deposition, thermal chemical vapor deposition and photochemical vapor deposition, etc. The present application does not limit the type and specific process of the second deposition treatment, and those skilled in the art can design it according to the final characteristic parameters of the carbon intermediate layer.
[0161] In some embodiments, the temperature of the second deposition treatment is 600°C to 1200°C, specifically 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0162] In some embodiments, the time of the second deposition treatment is 1 h to 20 h, specifically, 1 h, 3 h, 5 h, 10 h, 13 h, 15 h or 20 h, etc. Of course, it can also be other values within the above range, which is not limited here.
[0163] S200 , using a silicon source to perform a first deposition process in at least one of the first pores 12 , the second pores 14 and the third pores 16 of the porous carbonaceous material 1 , to obtain a negative electrode material.
[0164] In this step, since at least the first pore 12 is connected to the second pore 14, at least the second pore 14 is connected to the third pore 16, and at least the third pore 16 is connected to the surface of the negative electrode material, the silicon material 2 can be filled into the pores of at least one of the first pore 12, the second pore 14 and the third pore 16 through a deposition process. The combination method of the silicon material 2 and the porous carbonaceous material 1 can obtain a negative electrode material with a relatively dense structure, which is beneficial to improving the comprehensive performance of the material.
[0165] In some embodiments, the first deposition process comprises chemical vapor deposition.
[0166] In some embodiments, the deposition temperature of the chemical vapor deposition method is 375°C to 625°C, specifically 375°C, 400°C, 425°C, 475°C, 500°C, 550°C, 575°C, 600°C or 625°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0167] In some embodiments, the deposition time of the chemical vapor deposition method is 1 h to 20 h, specifically 1 h, 3 h, 5 h, 10 h, 13 h, 15 h or 20 h, etc., and of course, it can also be other values within the above range, which is not limited here.
[0168] In some embodiments, the silicon source includes at least one of monosilane and disilane.
[0169] In some embodiments, the inlet flow rate of the silicon source is 0.1 L / min to 10 L / min, specifically 0.1 L / min, 1 L / min, 3 L / min, 5 L / min, 7 L / min, 9 L / min or 10 L / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0170] In some embodiments, after performing a first deposition treatment using a silicon source in at least one of the first pores 12, the second pores 14, and the third pores 16 of the porous carbonaceous material 1, the method further includes: performing a third deposition treatment on the surface of the porous carbonaceous material 1 using a second carbon source to obtain a carbon coating layer coated on the surface of the porous carbonaceous material 1.
[0171] In some embodiments, the second carbon source includes at least one of dopamine, resorcinol-formaldehyde resin, glucose, sucrose, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, asphalt, anthracene, aniline, methanol, ethanol, acetic acid, sodium acetate, methane, ethane, propane, ethylene, propylene, propyne or acetylene.
[0172] In some embodiments, the third deposition process includes chemical vapor deposition. Exemplarily, the chemical vapor deposition method includes atmospheric pressure chemical vapor deposition, low pressure chemical vapor deposition, plasma chemical vapor deposition, thermal chemical vapor deposition, photochemical vapor deposition, and the like.
[0173] In some embodiments, the temperature of the third deposition treatment is 600°C to 1200°C, specifically 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C or 1200°C, etc. Of course, it can also be other values within the above range, which is not limited here.
[0174] In some embodiments, the time of the third deposition treatment is 0.5 h to 5 h, and specifically may be 0.5 h, 1 h, 2 h, 3 h, 4 h or 5 h, etc. Of course, it may also be other values within the above range, which is not limited here.
[0175] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises a negative electrode material prepared by the above preparation method.
[0176] Although the embodiments of the present invention are described, the present invention is not limited to these examples unless it exceeds the gist of the present invention.
[0177] Example 1
[0178] (1) A porous carbonaceous particle is provided, wherein the porous carbonaceous particle is obtained by manual screening, and the porous carbonaceous particle includes a first region 11 located in the central region inside the porous carbonaceous particle, a second region 13 covered on the surface of the first region 11, and a third region 15 covered on the surface of the second region 13, the porous carbonaceous particle located in the first region 11 has a first pore 12, the porous carbonaceous particle located in the second region 13 has a second pore 14, the porous carbonaceous particle located in the third region 15 has a third pore 16, the first pore 12 is connected to the second pore 14, the second pore 14 is connected to the third pore 16, the third pore 16 is connected to the surface of the porous carbonaceous particle, and the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.8 nm to 1.5 nm. 2 The pore size R of the third pore 16 is 2.3 nm to 3.0 nm. 3 The particle size is 13 nm to 50 nm, the probability entropy H of the pores in the porous carbonaceous particles is 0.952, and no other conditions are required.
[0179] (2) The porous carbonaceous particles obtained in (1) are loaded into a CVD furnace, and methane is used as a reactant to deposit a carbon intermediate layer in the porous carbon skeleton. The methane flow rate is 5 L / min, the deposition temperature is 900°C, and the deposition time is 200 min. The obtained carbon intermediate layer has a thickness of 10 nm and a fixed carbon content of 99.2%.
[0180] (3) The porous carbonaceous particles containing the intermediate layer obtained in (2) are treated with monosilane as the working gas, the deposition temperature is 500°C, the deposition time is 10 h, and the flow rate of monosilane is 2 L / min to obtain a material with a D50 of 2 nm.
[0181] (4) Using propylene as a carbon source, the material obtained in (3) was placed in a gas-coated rotary furnace, propane gas was introduced, and Ar gas was used as a protective atmosphere. Carbonization was carried out at 900°C, the propylene flow rate was 6 L / min, and the deposition time was 150 min to obtain a negative electrode material.
[0182] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 90nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 18%, and the proportion of micropores is 92%; the proportion of mesopores in the second pore 14 is 40%, and the proportion of micropores is 60%; the proportion of mesopores in the third pore 16 is 88%, and the proportion of macropores is 12%. The mass proportion of porous carbonaceous particles in the negative electrode material is 34%, the mass proportion of silicon particles in the negative electrode material is 66%, and the mass ratio of silicon element to carbon element is 1.20:1.
[0183] The calculation of H is as follows: For the negative electrode material of this embodiment, the corresponding relationship between Pi and n is as follows:
[0184]
[0185]
[0186] Then H = -(2*0.09log 18 (0.09)+2*0.06log 18 (0.06)+4*0.065log 18 (0.065)+4*0.045log 18 (0.045)+4*0.015og 18 (0.015)+2*0.1log 18 (0.1))=0.952
[0187] Example 2
[0188] Different from Example 1, in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.6 nm to 1.7 nm. 2 The pore size R of the third pore 16 is 1.8 nm to 3.4 nm. 3 The diameter of the pores in the porous carbonaceous particles is 21nm~42nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.72.
[0189] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 70%:25%:5%; the thickness of the third region 15 is 110nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 4900nm, the proportion of mesopores in the first pore 12 is 10%, and the proportion of micropores is 90%; the proportion of mesopores in the second pore 14 is 50%, and the proportion of micropores is 50%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 38%, the mass proportion of silicon particles in the negative electrode material is 62%, and the mass ratio of silicon element to carbon element is 0.9:1.
[0190] Example 3
[0191] Different from Example 1, in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.5 nm to 1.8 nm. 2 The pore size R of the third pore 16 is 2.3 nm to 4.5 nm. 3 The diameter of the pores in the porous carbonaceous particles is 16nm~47nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.80.
[0192] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 75%:15%:10%; the thickness of the third region 15 is 150nm, the thickness of the second region 13 is 1700nm, the thickness of the first region 11 is 5300nm, the proportion of mesopores in the first pore 12 is 5%, and the proportion of micropores is 95%; the proportion of mesopores in the second pore 14 is 35%, and the proportion of micropores is 65%; the proportion of mesopores in the third pore 16 is 90%, and the proportion of macropores is 10%. The mass proportion of porous carbonaceous particles in the negative electrode material is 45%, the mass proportion of silicon particles in the negative electrode material is 55%, and the mass ratio of silicon element to carbon element is 1.13:1.
[0193] Example 4
[0194] Different from Example 1, in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.2 nm to 0.7 nm. 2 The pore size R of the third pore 16 is 3 nm to 3.5 nm. 3 The size of the pores in the porous carbonaceous particles is 4nm to 12nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.95.
[0195] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 65%:25%:10%; the thickness of the third region 15 is 75nm, the thickness of the second region 13 is 1550nm, the thickness of the first region 11 is 5100nm, the proportion of mesopores in the first pore 12 is 7%, and the proportion of micropores is 93%; the proportion of mesopores in the second pore 14 is 45%, and the proportion of micropores is 55%; the proportion of mesopores in the third pore 16 is 92%, and the proportion of macropores is 8%. The mass proportion of porous carbonaceous particles in the negative electrode material is 56%, the mass proportion of silicon particles in the negative electrode material is 44%, and the mass ratio of silicon element to carbon element is 1.15:1.
[0196] Example 5
[0197] (1) A porous carbonaceous particle is provided, wherein the porous carbonaceous particle is obtained by 3D printing technology, and the porous carbonaceous particle includes a first region 11 located in the central region inside the porous carbonaceous particle, a second region 13 covered on the surface of the first region 11, and a third region 15 covered on the surface of the second region 13, the porous carbonaceous particle located in the first region 11 has a first pore 12, the porous carbonaceous particle located in the second region 13 has a second pore 14, and the porous carbonaceous particle located in the third region 15 has a third pore 16, the first pore 12 is connected to the second pore 14, the second pore 14 is connected to the third pore 16, and the third pore 16 is connected to the surface of the negative electrode material, and the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.8 nm to 1.5 nm. 2 The pore size R of the third pore 16 is 2.3 nm to 3 nm. 3 The diameter of the pores in the porous carbonaceous particles is 13 nm to 50 nm, the probability entropy H of the pores in the porous carbonaceous particles is 0.9, and the volume of the pores with a diameter of 0.5 nm to 5 nm accounts for 50% of the total pores in the porous carbonaceous particles.
[0198] (2) The porous carbonaceous particles obtained in (1) are loaded into a CVD furnace, and methane is used as a reactant to deposit a carbon intermediate layer in the porous carbon skeleton. The methane flow rate is 5 L / min, the deposition temperature is 900°C, and the deposition time is 200 min. The obtained carbon intermediate layer has a thickness of 10 nm, a fixed carbon content of 99.2%, and a mass percentage of 3%.
[0199] (3) The porous carbonaceous particles containing the intermediate layer obtained in (2) are treated with monosilane as the working gas, the deposition temperature is 500°C, the deposition time is 10 h, and the flow rate of monosilane is 2 L / min to obtain a material with a D50 of 2 nm.
[0200] (4) Using propylene as a carbon source, the material obtained in (3) was placed in a gas-coated rotary furnace, propane gas was introduced, and Ar gas was used as a protective atmosphere. Carbonization was carried out at 900°C, the propylene flow rate was 6 L / min, and the deposition time was 150 min to obtain a negative electrode material.
[0201] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 75%:20%:5%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4900nm, the proportion of mesopores in the first pore 12 is 20%, and the proportion of micropores is 80%; the proportion of mesopores in the second pore 14 is 40%, and the proportion of micropores is 60%; the proportion of mesopores in the third pore 16 is 90%, and the proportion of macropores is 10%. The mass proportion of porous carbonaceous particles in the negative electrode material is 32%, the mass proportion of silicon particles in the negative electrode material is 65%, and the mass ratio of silicon element to carbon element is 1.3:1.
[0202] Example 6
[0203] Different from Example 5, in step (1), the volume proportion of the openings with a pore size of 0.5 nm to 5 nm in the total pores in the porous carbonaceous particles is 45%.
[0204] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 71%:20%:9%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 5200nm, the proportion of mesopores in the first pore 12 is 40%, and the proportion of micropores is 60%; the proportion of mesopores in the second pore 14 is 72%, and the proportion of micropores is 68%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 35%, the mass proportion of silicon particles in the negative electrode material is 65%, and the mass ratio of silicon element to carbon element is 1.20:1.
[0205] Example 7
[0206] The difference from Example 5 is that in step (1), the volume proportion of the openings with a pore size of 0.5 nm to 5 nm in the total pores in the porous carbonaceous particles is 65%.
[0207] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 72%:18%:10%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1200nm, the thickness of the first region 11 is 5100nm, the proportion of mesopores in the first pore 12 is 5%, and the proportion of micropores is 95%; the proportion of mesopores in the second pore 14 is 35%, and the proportion of micropores is 65%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 36%, the mass proportion of silicon particles in the negative electrode material is 64%, and the mass ratio of silicon element to carbon element is 1.22:1.
[0208] Example 8
[0209] The difference from Example 5 is that in step (1), the volume proportion of the openings with a pore size of 0.5 nm to 5 nm in the total pores in the porous carbonaceous particles is 70%.
[0210] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 74%:20%:6%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1300nm, the thickness of the first region 11 is 5400nm, the proportion of mesopores in the first pore 12 is 20%, and the proportion of micropores is 80%; the proportion of mesopores in the second pore 14 is 32%, and the proportion of micropores is 68%; the proportion of mesopores in the third pore 16 is 90%, and the proportion of macropores is 10%. The mass proportion of porous carbonaceous particles in the negative electrode material is 30%, the mass proportion of silicon particles in the negative electrode material is 70%, and the mass ratio of silicon element to carbon element is 1.22:1.
[0211] Example 9
[0212] The difference from Example 5 is that in step (1), the volume proportion of the openings with a pore size of 0.5 nm to 5 nm in the total pores in the porous carbonaceous particles is 80%.
[0213] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 78%:22%:10%; the thickness of the third region 15 is 80nm, the thickness of the second region 13 is 1200nm, the thickness of the first region 11 is 5400nm, the proportion of mesopores in the first pore 12 is 25%, and the proportion of micropores is 75%; the proportion of mesopores in the second pore 14 is 32%, and the proportion of micropores is 68%; the proportion of mesopores in the third pore 16 is 95%, and the proportion of macropores is 5%. The mass proportion of porous carbonaceous particles in the negative electrode material is 30%, the mass proportion of silicon particles in the negative electrode material is 70%, and the mass ratio of silicon element to carbon element is 1.28:1.
[0214] Example 10
[0215] The difference from Example 5 is that in step (1), the volume proportion of the openings with a pore size of 0.5 nm to 5 nm in the total pores in the porous carbonaceous particles is 85%.
[0216] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 5000nm, the proportion of mesopores in the first pore 12 is 10%, and the proportion of micropores is 90%; the proportion of mesopores in the second pore 14 is 35%, and the proportion of micropores is 65%; the proportion of mesopores in the third pore 16 is 95%, and the proportion of macropores is 5%. The mass proportion of porous carbonaceous particles in the negative electrode material is 34%, the mass proportion of silicon particles in the negative electrode material is 66%, and the mass ratio of silicon element to carbon element is 1.26:1.
[0217] Embodiment 11
[0218] (1) Providing porous carbonaceous particles, wherein the porous carbonaceous particles are obtained by manual screening, the porous carbonaceous particles comprising a first region 11 located in the central region of the porous carbonaceous particles, a second region 13 covering the surface of the first region 11, and a third region 15 covering the surface of the second region 13, the porous carbonaceous particles located in the first region 11 have a first pore 12, the porous carbonaceous particles located in the second region 13 have a second pore 14, the porous carbonaceous particles located in the third region 15 have a third pore 16, the first pore 12 is connected to the second pore 14, the second pore 14 is connected to the third pore 16, the third pore 16 is connected to the surface of the negative electrode material, the pore size R1 of the first pore 12 is 0.8-1.5 nm, the pore size R2 of the second pore 14 is 2.3-3 nm, the pore size R3 of the third pore 16 is 13-50 nm, the probability entropy H of the pores in the porous carbonaceous particles is 0.9, and the pore volume of the porous carbonaceous particles is 0.4 cm 3 / g.
[0219] (2) The porous carbonaceous particles obtained in (1) are loaded into a CVD furnace, and methane is used as a reactant to deposit a carbon intermediate layer in the porous carbon skeleton. The methane flow rate is 5 L / min, the deposition temperature is 900°C, and the deposition time is 200 min. The obtained carbon intermediate layer has a thickness of 10 nm, a fixed carbon content of 99.2%, and a mass percentage of 3%.
[0220] (3) The porous carbonaceous particles containing the intermediate layer obtained in (2) are treated with monosilane as the working gas, the deposition temperature is 500°C, the deposition time is 10 h, and the flow rate of monosilane is 2 L / min to obtain a material with a D50 of 2 nm.
[0221] (4) Using propylene as a carbon source, the material obtained in (3) was placed in a gas-coated rotary furnace, propane gas was introduced, and Ar gas was used as a protective atmosphere. Carbonization was carried out at 900°C, the propylene flow rate was 6 L / min, and the deposition time was 150 min to obtain a negative electrode material.
[0222] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 79%:15%:6%; the thickness of the third region 15 is 80nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 4600nm, the proportion of mesopores in the first pore 12 is 17%, and the proportion of micropores is 93%; the proportion of mesopores in the second pore 14 is 45%, and the proportion of micropores is 55%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 25%, the mass proportion of silicon particles in the negative electrode material is 75%, and the mass ratio of silicon element to carbon element is 1.27:1.
[0223] Example 12
[0224] Different from Example 11, in step (1), the pore volume of the porous carbonaceous particles is 0.7 cm 3 / g.
[0225] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:20%:7%; the thickness of the third region 15 is 110nm, the thickness of the second region 13 is 1200nm, the thickness of the first region 11 is 5000nm, the proportion of mesopores in the first pore 12 is 30%, and the proportion of micropores is 70%; the proportion of mesopores in the second pore 14 is 42%, and the proportion of micropores is 58%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 40%, the mass proportion of silicon particles in the negative electrode material is 60%, and the mass ratio of silicon element to carbon element is 1.23:1.
[0226] Embodiment 13
[0227] Different from Example 11, in step (1), the pore volume of the porous carbonaceous particles is 1 cm 3 / g.
[0228] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 90nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 10%, and the proportion of micropores is 90%; the proportion of mesopores in the second pore 14 is 40%, and the proportion of micropores is 60%; the proportion of mesopores in the third pore 16 is 84%, and the proportion of macropores is 16%. The mass proportion of porous carbonaceous particles in the negative electrode material is 27%, the mass proportion of silicon particles in the negative electrode material is 73%, and the mass ratio of silicon element to carbon element is 1.25:1.
[0229] Embodiment 14
[0230] Different from Example 11, in step (1), the pore volume of the porous carbonaceous particles is 1.2 cm 3 / g.
[0231] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 90nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 15%, and the proportion of micropores is 85%; the proportion of mesopores in the second pore 14 is 35%, and the proportion of micropores is 65%; the proportion of mesopores in the third pore 16 is 82%, and the proportion of macropores is 18%. The mass proportion of porous carbonaceous particles in the negative electrode material is 25%, the mass proportion of silicon particles in the negative electrode material is 75%, and the mass ratio of silicon element to carbon element is 1.27:1.
[0232] Embodiment 15
[0233] (1) A porous carbonaceous particle is provided, wherein the porous carbonaceous particle is obtained by manual screening, and the porous carbonaceous particle includes a first region 11 located in the central region inside the porous carbonaceous particle, a second region 13 covered on the surface of the first region 11, and a third region 15 covered on the surface of the second region 13, the porous carbonaceous particle located in the first region 11 has a first pore 12, the porous carbonaceous particle located in the second region 13 has a second pore 14, the porous carbonaceous particle located in the third region 15 has a third pore 16, the first pore 12 is connected to the second pore 14, the second pore 14 is connected to the third pore 16, the third pore 16 is connected to the surface of the negative electrode material, and the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.8 to 1.5 nm. 2 The pore size R of the third pore 16 is 2.3-3 nm. 3The diameter of the porous carbon particles is 13-50 nm, the probability entropy H of the pores in the porous carbon particles is 0.9, and the number of open pores in the porous carbon particles accounts for 80% of the total number of pores in the porous carbon particles.
[0234] (2) The porous carbonaceous particles obtained in (1) are loaded into a CVD furnace, and methane is used as a reactant to deposit a carbon intermediate layer in the porous carbon skeleton. The methane flow rate is 5 L / min, the deposition temperature is 900°C, and the deposition time is 200 min. The obtained carbon intermediate layer has a thickness of 10 nm, a fixed carbon content of 99.2%, and a mass percentage of 3%.
[0235] (3) The porous carbonaceous particles containing the intermediate layer obtained in (2) are treated with monosilane as the working gas, the deposition temperature is 500°C, the deposition time is 10 h, and the flow rate of monosilane is 2 L / min to obtain a material with a D50 of 2 nm.
[0236] (4) Using propylene as a carbon source, the material obtained in (3) was placed in a gas-coated rotary furnace, propane gas was introduced, and Ar gas was used as a protective atmosphere. Carbonization was carried out at 900°C, the propylene flow rate was 6 L / min, and the deposition time was 150 min to obtain a negative electrode material.
[0237] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 80%:11%:9%; the thickness of the third region 15 is 130nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 5000nm, the proportion of mesopores in the first pore 12 is 20%, and the proportion of micropores is 80%; the proportion of mesopores in the second pore 14 is 34%, and the proportion of micropores is 66%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 32%, the mass proportion of silicon particles in the negative electrode material is 68%, and the mass ratio of silicon element to carbon element is 1.21:1.
[0238] Example 16
[0239] Different from Example 15, in step (1), the number of open pores in the porous carbonaceous particles accounts for 82% of the total number of pores in the porous carbonaceous particles.
[0240] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 80%:20%:10%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 20%, and the proportion of micropores is 80%; the proportion of mesopores in the second pore 14 is 45%, and the proportion of micropores is 55%; the proportion of mesopores in the third pore 16 is 88%, and the proportion of macropores is 12%. The mass proportion of porous carbonaceous particles in the negative electrode material is 30%, the mass proportion of silicon particles in the negative electrode material is 70%, and the mass ratio of silicon element to carbon element is 1.23:1.
[0241] Embodiment 17
[0242] Different from Example 15, in step (1), the number of open pores in the porous carbonaceous particles accounts for 88% of the total number of pores in the porous carbonaceous particles.
[0243] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 75%:20%:5%; the thickness of the third region 15 is 80nm, the thickness of the second region 13 is 1300nm, the thickness of the first region 11 is 5100nm, the proportion of mesopores in the first pore 12 is 15%, and the proportion of micropores is 85%; the proportion of mesopores in the second pore 14 is 32%, and the proportion of micropores is 68%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 38%, the mass proportion of silicon particles in the negative electrode material is 62%, and the mass ratio of silicon element to carbon element is 1.21:1.
[0244] Embodiment 18
[0245] Different from Example 15, in step (1), the number of open pores in the porous carbonaceous particles accounts for 94% of the total number of pores in the porous carbonaceous particles.
[0246] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:20%:7%; the thickness of the third region 15 is 90nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 18%, and the proportion of micropores is 92%; the proportion of mesopores in the second pore 14 is 35%, and the proportion of micropores is 65%; the proportion of mesopores in the third pore 16 is 85%, and the proportion of macropores is 15%. The mass proportion of porous carbonaceous particles in the negative electrode material is 30%, the mass proportion of silicon particles in the negative electrode material is 70%, and the mass ratio of silicon element to carbon element is 1.29:1.
[0247] Embodiment 19
[0248] Different from Example 15, in step (1), the number of open pores in the porous carbonaceous particles accounts for 99% of the total number of pores in the porous carbonaceous particles.
[0249] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 90nm, the thickness of the second region 13 is 1000nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 30%, and the proportion of micropores is 70%; the proportion of mesopores in the second pore 14 is 38%, and the proportion of micropores is 62%; the proportion of mesopores in the third pore 16 is 92%, and the proportion of macropores is 8%. The mass proportion of porous carbonaceous particles in the negative electrode material is 27%, the mass proportion of silicon particles in the negative electrode material is 73%, and the mass ratio of silicon element to carbon element is 1.30:1.
[0250] Comparative Example 1
[0251] The difference from Example 1 is that in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 2.3 nm to 2.8 nm. 2 The pore size R of the third pore 16 is 5.2 nm to 10 nm. 3 The size of the pores in the porous carbonaceous particles is 70nm~100nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.9.
[0252] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 4800nm, the proportion of mesopores in the first pore 12 is 100%; the proportion of mesopores in the second pore 14 is 100%; the proportion of mesopores in the third pore 16 is 61%, and the proportion of macropores is 39%. The mass proportion of porous carbonaceous particles in the negative electrode material is 62%, the mass proportion of silicon particles in the negative electrode material is 38%, and the mass ratio of silicon element to carbon element is 0.6:1.
[0253] Comparative Example 2
[0254] The difference from Example 1 is that in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 2.3 nm to 2.8 nm. 2 The pore size R of the third pore 16 is 2.3 nm to 3 nm. 3 The diameter of the pores in the porous carbonaceous particles is 13nm~50nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.9.
[0255] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 80%:13%:7%; the thickness of the third region 15 is 110nm, the thickness of the second region 13 is 1200nm, the thickness of the first region 11 is 5200nm, the proportion of mesopores in the first pore 12 is 100%; the proportion of mesopores in the second pore 14 is 100%; the proportion of mesopores in the third pore 16 is 100%. The mass proportion of porous carbonaceous particles in the negative electrode material is 60%, the mass proportion of silicon particles in the negative electrode material is 40%, and the mass ratio of silicon element to carbon element is 0.7:1.
[0256] Comparative Example 3
[0257] The difference from Example 1 is that in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.8 nm to 1.5 nm. 2 The pore size R of the third pore 16 is 5.8 nm to 8.2 nm. 3 The size of the pores is 13nm~50nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.87.
[0258] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 75%:15%:10%; the thickness of the third region 15 is 90nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 5000nm, the proportion of mesopores in the first pore 12 is 35%, and the proportion of micropores is 65%; the proportion of mesopores in the second pore 14 is 100%; the proportion of mesopores in the third pore 16 is 100%. The mass proportion of porous carbonaceous particles in the negative electrode material is 58%, the mass proportion of silicon particles in the negative electrode material is 42%, and the mass ratio of silicon element to carbon element is 0.8:1.
[0259] Comparative Example 4
[0260] The difference from Example 1 is that in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.8 nm to 1.5 nm. 2 The pore size R of the third pore 16 is 1.8 nm to 2.5 nm. 3 The particle size is 2.0 nm to 2.7 nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.87.
[0261] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 78%:15%:7%; the thickness of the third region 15 is 110nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 5300nm, the proportion of mesopores in the first pore 12 is 25%, and the proportion of micropores is 75%; the proportion of mesopores in the second pore 14 is 68%, and the proportion of micropores is 32%; the proportion of mesopores in the third pore 16 is 100%. The mass proportion of porous carbonaceous particles in the negative electrode material is 38%, the mass proportion of silicon particles in the negative electrode material is 62%, and the mass ratio of silicon element to carbon element is 1.0:1.
[0262] Comparative Example 5
[0263] The difference from Example 1 is that in step (1), the pore size R of the first pore 12 is 1 The pore size R of the second pore 14 is 0.8 nm to 1.5 nm. 2 The pore size R of the third pore 16 is 2.3 nm to 3 nm. 3 The size of the pores is 13nm~50nm, and the probability entropy H of the pores in the porous carbonaceous particles is 0.66.
[0264] In the negative electrode material obtained in this embodiment, the volume ratio of the first region 11, the second region 13 and the third region 15 is 73%:19%:8%; the thickness of the third region 15 is 100nm, the thickness of the second region 13 is 1100nm, the thickness of the first region 11 is 4700nm, the proportion of mesopores in the first pore 12 is 20%, and the proportion of micropores is 80%; the proportion of mesopores in the second pore 14 is 100%; the proportion of mesopores in the third pore 16 is 88%. The mass proportion of porous carbonaceous particles in the negative electrode material is 30%, the mass proportion of silicon particles in the negative electrode material is 70%, and the mass ratio of silicon element to carbon element is 0.9:1.
[0265] Performance Test:
[0266] 1. Open and closed pore quantity test: low carbon residue resin is used as the inlay resin sample, polished, and then the inlay resin is ablated clean under an inert protective atmosphere to obtain the test sample. The open and closed pore data are counted through the metallographic microscope system.
[0267] 2. Porosity, pore size and proportion test method: The amount of pores per unit weight of the material (cm 3 / g) and bulk density (g / cm 3). Porosity can therefore be expressed on a volume basis as (volume / volume). (Volume) density can be obtained by dividing the mass of a material by the volume of the sample. The amount of pores per unit weight can further be measured under well-known conditions and using nitrogen adsorption (micropores and mesopores) or mercury porosimeter (macroporous).
[0268] 3. Silicon particle size test method: Observe the nano-silicon particles through a field emission scanning electron microscope or a transmission electron microscope, directly measure the particle sizes of 5-10 nano-silicon particles through a scale, and take the average value of the particle size as the final nano-silicon particle size.
[0269] 4. The cross-sectional dimension diameter of a hole is the longest length measured in the cross section of the hole.
[0270] 5. D50 was measured using a laser particle size analyzer, and it showed a symmetrical distribution similar to a normal distribution. In its volume-based distribution, the cumulative 50% diameter was D50.
[0271] 6. The specific surface area was measured using the American Micromeritics TriStar 3000 specific surface area and pore size analyzer.
[0272] 7. The XRD peak was measured using a PANalytical X'pert Pro X-ray diffractometer, and then the C peak in the XRD was fitted using Jade 6.5 software to obtain the crystallite size of the C(002) peak.
[0273] 8. Prepare the negative electrode slurry according to the mass ratio of Si-C / C composite material, conductive carbon black and PPA of 75:15:10, apply it on copper foil, and make the negative electrode sheet after drying. Use metal lithium sheet as the counter electrode and assemble it into button cells in a glove box filled with Ar gas. The button cell is charged and discharged at a current density of 0.1C in the charge and discharge range of 0.01-5V to obtain the first reversible specific capacity and ICE of the button cell.
[0274] 9. According to the mass ratio of Si-C / C composite material and graphite mixture, Super-P, KS-6, CMC, SBR is 92:2:2:2:2 to prepare negative electrode slurry, apply it on copper foil, and make negative electrode plate after drying. The proportion of Si-C and graphite in the Si-C composite material and graphite mixture is determined by the first reversible specific capacity of the two and the capacity required to be matched. With metal lithium sheet as the counter electrode, button cells are assembled in a glove box filled with Ar gas. At a current density of 1C, the button cell is charged and discharged 50 times in the charge and discharge range of 0.01V-5V to obtain the capacity retention rate and electrode thickness expansion rate after 50 cycles of the battery. The test results are shown in Tables 1 and 2.
[0275] Table 1. Parameters of porous carbonaceous particles of Examples and Comparative Examples
[0276]
[0277]
[0278] Table 2. Parameters and electrochemical properties of negative electrode materials prepared in experimental examples and comparative examples
[0279]
[0280]
[0281] Through the data in Tables 1 and 2 of the results of the comparative examples and embodiment tests, it can be found that: in the negative electrode material of the present application, the probability entropy H of the pores in the porous carbonaceous material 1 satisfies: 0.96>H>0.70, so that the porous carbonaceous material 1 has a relatively uniform pore distribution and a relatively dense structure, and the porous carbonaceous material 1 has a tendency of increasing pore size from the inside to the surface of the porous carbonaceous material 1, and the first pore 12, the second pore 14 and the third pore 16 are connected to form a pore network, and the silicon material 2 is embedded in the above-mentioned pore network, which can produce capillary action to absorb part of the electrolyte, increase the liquid retention amount of the electrolyte, and is beneficial to improve the cycle life of the negative electrode material. The negative electrode material of the present application is a negative electrode material with a relatively dense structure, which is beneficial to control the degree of lithium ion transmission and ensure the effectiveness of lithium ion embedding and extraction, thereby ensuring the low expansion and structural stability of the negative electrode material, and has excellent specific capacity, initial efficiency and cycle life.
[0282] In the negative electrode material prepared in comparative example 1, the pore size arrangement and probability entropy of the first pore 12, the second pore 14 and the third pore 16 do not conform to the distribution law specified in the present application, resulting in that during the preparation of the negative electrode material, the silicon source gas cannot effectively penetrate into the interior of the porous carbonaceous material 1 from the outside to the inside, and the silicon content filled in the particles is small and uneven, resulting in a large number of pores in the negative electrode material, resulting in insufficient strength of the negative electrode material during the preparation of the electrode sheet, and the particles are easily broken, which reduces the specific capacity, initial efficiency and cycle performance of the negative electrode material.
[0283] In Comparative Example 2, the pore size of the first pore 12 is too large and does not meet the specified range of the present application. The pore sizes of the first pore 12 and the second pore 14 in the negative electrode material are in almost the same range. Although the larger first pore size makes it easier for the silicon source gas to enter the pores, it will cause the internal pore filling rate of the first pore 12 region to decrease. On the one hand, this will lead to a decrease in particle strength and make it easier to break during the preparation of the electrode sheet. As a result, the electrolyte can easily and quickly penetrate into the particles during the charge and discharge process, causing the SEI film to continue to thicken and the electrochemical performance to deteriorate. On the other hand, this will also cause a waste of internal filling, that is, the silicon loading amount is reduced compared to the gradually shrinking pore distribution, which will also lead to deterioration of the electrochemical performance.
[0284] In comparative example 3, the pore size of the second pore 14 is too large and does not meet the limited range of the present application. Although this will facilitate the diffusion of gas from the third pore 16 to the second pore 14, because the pore size difference between the second pore 14 and the first pore 12 is too large, it will cause a large amount of gas to flow into the first pore 12 at the same time due to the narrow channel when the gas enters the first pore 12 through the funnel effect, resulting in excessive instantaneous gas pressure, which is not conducive to the effective diffusion and deposition of gas. In addition, since the thickness of the second pore 14 is 50nm to 2000nm, its pore size is too large, which will lead to an excessive proportion of mesopores in the overall material, and there will be problems of uneven deposition and agglomeration of silicon particles, which will also lead to poor electrochemical performance of the final battery.
[0285] In Comparative Example 4, the pore size of the third pore 16 is too small to meet the requirements, and the pore sizes of the second pore 14 and the third pore 16 in the negative electrode material are in almost the same range. Although the overall reduction in the pore size of the negative electrode material will make the final product more dispersed and evenly distributed, the third pore 16, which is too narrow at the beginning, hinders the gas from diffusing to the second pore 14 and even further to the first pore 12, which will bring about the problem of partial sealing of the particle surface. In this way, too few silicon particles are deposited in the later stage, and the specific capacity and initial efficiency of the material will be affected, and the cycle performance will also be reduced.
[0286] In the negative electrode material prepared in Comparative Example 5, the pore size arrangement of the first pore 12, the second pore 14 and the third pore 16 conforms to the distribution law specified in the present application, while the probability entropy does not conform to the specified conditions of the present application. The pore distribution in the prepared negative electrode material is uneven, resulting in uneven stress inside the particles of the negative electrode material. Cracks are prone to occur in areas where silicon is more distributed, resulting in pulverization and breakage of the particles, and easy infiltration of electrolyte. The generated SEI film is relatively thick, resulting in low discharge specific capacity and impedance of the material. At the same time, the generated SEI film will continue to thicken during the cyclic charge and discharge process, resulting in poor cycle performance of the negative electrode material.
[0287] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A negative electrode material, characterized in that: The negative electrode material includes a porous carbonaceous material and a silicon material. The negative electrode material has a first region located in the central region inside the porous carbonaceous material, a second region distributed on the surface of the first region, and a third region distributed on the surface of the second region. The porous carbonaceous material located in the first region has a first pore, the porous carbonaceous material located in the second region has a second pore, and the porous carbonaceous material located in the third region has a third pore. At least part of the first pore is connected to the second pore, at least part of the second pore is connected to the third pore, and at least part of the third pore is connected to the surface of the negative electrode material. The silicon material is distributed in at least one of the first pore, the second pore and the third pore. The pore diameter of the first pore is 0.1nm~2.2nm, the pore diameter of the second pore is 1.8nm~5nm, and the pore diameter of the third pore is 3nm~60nm. The probability entropy H of the pores in the porous carbonaceous material satisfies: 0.96>H>0.
70.
2. The negative electrode material according to claim 1, characterized in that The negative electrode material includes at least one of the following features (1) to (14): (1) the first pores include micropores, and the number of micropores in the first pores accounts for more than 60% based on the total number of pores in the first pores being 100%; (2) the first pores include mesopores, and the number of mesopores in the first pores accounts for 5% to 40% based on the total number of pores in the first pores being 100%; (3) the second pores include micropores, and the number of micropores in the second pores accounts for less than 70% based on the total number of pores in the second pores being 100%; (4) the second pores include mesopores, and the number of mesopores in the second pores accounts for 30% to 90% based on the total number of pores in the second pores as 100%; (5) the third pores include macropores, and the number of macropores in the third pores accounts for less than 20% based on the total number of pores in the third pores being 100%; (6) The third pores include mesopores, and the number of mesopores in the third pores accounts for 80% to 95% based on the total number of pores in the third pores as 100%; (7) The volume ratio of the first region, the second region and the third region is (0.6-0.8):(0.1-0.4):(0-0.1) (excluding 0); (8) The thickness H1 of the first region, the thickness H2 of the second region, and the thickness H3 of the third region satisfy: H1>H2>H3; (9) The thickness H3 of the first region is 130 nm to 13000 nm; (10) The thickness H2 of the second region is 50 nm to 2000 nm; (11) The thickness H1 of the third region is 20 nm to 1000 nm; (12) The pores in the porous carbonaceous material include open pores, and the number of the open pores accounts for 82% to 99% of the total number of pores in the porous carbonaceous material; (13) The pores in the porous carbonaceous material include open pores, and the volume proportion of the open pores with a pore size of 0.2 nm to 10 nm in the total pores in the porous carbonaceous material is 50% to 80%; (14) The pores in the negative electrode material include open pores, and the volume proportion of the open pores with a pore size of 0.5 nm to 5 nm in the total pores in the negative electrode material is 55% to 75%.
3. The negative electrode material according to claim 1, characterized in that The negative electrode material includes at least one of the following features (1) to (23): (1) The silicon material is also disposed on the surface of the porous carbonaceous material; (2) The porous carbonaceous material comprises at least one of petrochemical carbon, wood carbon and high molecular weight polymer carbon; (3) The silicon material includes at least one of elemental silicon, SiO x (0 < x < 2), and silicon alloys; (4) The particle size of the silicon material is 50% to 100% of the pore size of the porous carbon material; (5) The median particle size of the silicon material is 1 nm to 50 nm; (6) The morphology of the porous carbonaceous material includes at least one of a spherical shape and a quasi-spherical shape; (7) The median particle size of the porous carbonaceous material is 0.2 μm to 20 μm; (8) The standard deviation of the directional distribution of pores in the porous carbonaceous material is 0.5% to 2.0%; (9) The two-dimensional porosity of the porous carbonaceous material is 40% to 65%; (10) The three-dimensional porosity of the porous carbonaceous material is 45% to 70%; (11) The porous carbonaceous material accounts for 25% to 75% by mass of the negative electrode material; (12) The mass proportion of the silicon material in the negative electrode material is 25% to 75%; (13) The mass ratio of silicon element to carbon element in the negative electrode material is (0.8-1.5):1; (14) The pore size of the porous carbonaceous material is 0.05 nm to 80 nm; (15) The porous carbonaceous material is measured by X-ray diffraction, and the interlayer spacing of the (002) plane is 0.3 nm to 0.5 nm; (16) The specific surface area of the porous carbonaceous material is 1000 m 2 / g~3000m 2 / g; (17) The fixed carbon content of the porous carbonaceous material is greater than or equal to 99.5%; (18) The pore volume of the porous carbonaceous material is greater than or equal to 0.6 cm 3 / g; (19) In the porous carbonaceous material, sp 3 The content of hybrid carbon is 50% to 80%; (20) The two-dimensional porosity of the negative electrode material is 1% to 30%; (21) The three-dimensional porosity of the negative electrode material is 2% to 25%; (22) The specific surface area of the negative electrode material is 1.5 m 2 / g~100m 2 / g; (23) The median particle size of the silicon material is 1 nm to 50 nm.
4. The negative electrode material according to claim 1, characterized in that The negative electrode material further includes a carbon intermediate layer disposed between the silicon material and a pore wall of at least one of the first pore, the second pore, and the third pore; The carbon intermediate layer includes at least one of the following features (1) to (3): (1) The material of the carbon intermediate layer includes at least one of carbon nanotubes, carbon fibers and graphene; (2) The fixed carbon content of the carbon intermediate layer is greater than or equal to 99%; (3) The thickness of the carbon intermediate layer is 0.1 nm to 5 nm.
5. The negative electrode material according to claim 1, characterized in that The negative electrode material further includes a coating layer covering at least a portion of the surface of the porous carbonaceous material, and the negative electrode material includes at least one of the following features (1) to (3): (1) The material of the coating layer includes at least one of carbon black, graphite, carbon fiber, carbon nanotube and graphene; (2) The coating layer has a thickness of 2 nm to 100 nm; (3) The coating layer accounts for 1% to 10% by mass of the negative electrode material.
6. A method for preparing a negative electrode material, characterized in that: The steps include: A porous carbonaceous material is provided, wherein the porous carbonaceous material has a first region located in the central region inside the negative electrode material, a second region distributed on the surface of the first region, and a third region distributed on the surface of the second region, the porous carbonaceous material located in the first region has a first pore, the porous carbonaceous material located in the second region has a second pore, the porous carbonaceous material located in the third region has a third pore, at least part of the first pore is connected to the second pore, at least part of the second pore is connected to the third pore, at least part of the third pore is connected to the surface of the porous carbonaceous material, the pore size of the first pore is 0.1nm-2.2nm, the pore size of the second pore is 1.8nm-5nm, the pore size of the third pore is 3nm-60nm, and the probability entropy H of the pores in the porous carbonaceous material satisfies: 0.96>H>0.70; A silicon source is used to perform a first deposition process in at least one of the first pores, the second pores and the third pores of the porous carbonaceous material to obtain a negative electrode material.
7. The preparation method according to claim 6, characterized in that: The preparation method comprises at least one of the following features (1) to (5): (1) The first deposition process comprises chemical vapor deposition; (2) The temperature of the first deposition treatment is 375° C. to 625° C.; (3) The first deposition treatment time is 1 h to 20 h; (4) The silicon source comprises at least one of monosilane and disilane; (5) The inlet flow rate of the silicon source is 0.1 L / min to 10 L / min.
8. The preparation method according to claim 6, characterized in that: Before performing a first deposition process in at least one of the first pores, the second pores, and the third pores of the porous carbonaceous material using a silicon source, the method further includes: performing a second deposition process in at least one of the first pores, the second pores, and the third pores of the porous carbonaceous material using a first carbon source; The preparation method comprises at least one of the following features (1) to (6): (1) The first carbon source includes gaseous hydrocarbons; (2) the first carbon source comprises gaseous hydrocarbons, wherein the gaseous hydrocarbons comprise at least one of methane, ethane, propane, ethylene, propylene, acetylene and propyne; (3) The flow rate of the first carbon source is 0.1 L / min to 20 L / min; (4) the second deposition process comprises at least one of a physical vapor deposition method and a chemical vapor deposition method; (5) The temperature of the second deposition treatment is 600° C. to 1200° C.; (6) The second deposition treatment time is 1 hour to 20 hours.
9. The preparation method according to claim 6, characterized in that: After performing a first deposition process in at least one of the first pores, the second pores and the third pores of the porous carbonaceous material using a silicon source, the method further includes: performing a third deposition process on the surface of the porous carbonaceous material using a second carbon source; The preparation method comprises at least one of the following features (1) to (4): (1) the second carbon source comprises at least one of dopamine, resorcinol-formaldehyde resin, glucose, sucrose, tannic acid, citric acid, polyvinyl alcohol, polypyrrole, vitamin C, polyethylene glycol, asphalt, anthracene, aniline, methanol, ethanol, acetic acid, sodium acetate, methane, ethane, propane, ethylene, propylene, propyne or acetylene; (2) the third deposition process comprises chemical vapor deposition; (3) The temperature of the third deposition process is 600° C. to 1200° C.; (4) The duration of the third deposition treatment is 0.5 h to 5 h.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode material according to any one of claims 1 to 5 or the negative electrode material prepared by the preparation method according to any one of claims 6 to 9.
Citation Information
Cited By
Solid-state battery, preparation method thereof and power utilization device
CN121076266A